Dampak Pertumbuhan PDB Perkapita, Pengeluaran Rumah Tangga Perkapita, Perdagangan Terbuka dan Laju Populasi Perkotaan Terhadap Konsumsi Energi Akhir Perumahan - Bambang Priyo Cahyono; Sitti Marijam Thawil; Sohirin Sohirin (MediaTrend, 2020)
The purpose of this study is to investigate the impact of GDP per capita, household final consumption expenditure per capita, openness trade, and urban population rate towards residential final energy consumption in Indonesia using annual data over the period 1977-2016. We applied is unit root test, cointegration test, and estimation of short and long term relationships based on the Autoregressive Distributed Lag (ARDL) procedures. Our results show that GDP per capita, open trade, and urban population growth rate have a significant impact on residential final energy consumption, while household final consumption expenditure did not influence the growth of residential final energy consumption in Indonesia. Based on these findings, we concluded that the growth of GDP per capita, household consumption expenditures, openness trade and the rate of urban population are relevant indicators to predicting the growth rate of residential energy consumption in Indonesia.